Demographic Factors and Self-compassion as Predictors of Positive Mental Health in Married Hindu Couples - Priyanka Parihar; Rishika Mishra; Shraddha Khare; Gyanesh Kumar Tiwari (Gonabad University of Medical Sciences, 2024)
Background: Research suggests that self-compassion is important for understanding different life outcomes. This study explored how certain demographic factors and self-compassion affect the positive mental health of married Hindu couples.  Methods: Utilizing a correlational design, 300 married Hindu couples (age range=26-50 years, Mean±SD, 38.42±7.89) from Sagar City, Madhya Pradesh, India, were recruited through snowball sampling, in which existing participants provided referrals to other potential participants. The self-compassion scale, the socioeconomic status scale and the mental health continuum-short form were used as study measures. Mean±SD, correlation and regression analysis were computed. The significance level was ≤0.05.  Results: The results revealed that age (r=0.188, P=0.01) marriage length (r=0.110, P=0.01), self-kindness (r=0.332, P=0.01), common humanity (r=0.284, P=0.01), and mindfulness (r=0.250, P=0.01) were positively correlated with well-being. Conversely, self-judgment (r=-0.099, P=NS), isolation (r=0.019, P=NS) and over-identification (r=0.005, P=NS) displayed weak or negative correlations. Demographic factors (education, gender, age, domicile, occupation and marriage length) (R2=12.6%, P<0.001) and self-compassion (R2=24.80%, P<0.001) significantly predicted well-being.  Conclusion: The findings provide significant insights into the positive role of self-compassion and demographic factors in the well-being of married Hindu couples. Future research could examine the role of self-compassion interventions in different cultural contexts and examine long-term well-being outcomes.